2011
DOI: 10.1016/j.ijid.2011.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leishmania parasites in the blood of patients with isolated cutaneous leishmaniasis

Abstract: In the current study, the detection rate of parasites in the blood of patients with cutaneous leishmaniasis was high. This illustrates the invasive characteristic of the parasite that has escaped the skin. Testing should be considered in areas other than Lebanon, especially around the Mediterranean basin. Whether these findings support the administration of systemic treatment for cutaneous leishmaniasis or not needs to be confirmed in larger prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
(40 reference statements)
0
12
0
1
Order By: Relevance
“…Further variation of the CL disease caused by L . donovani exists wherein the parasite is detected in blood culture with no visceral manifestation [ 37 ].…”
Section: Cutaneous Leishmaniasismentioning
confidence: 99%
“…Further variation of the CL disease caused by L . donovani exists wherein the parasite is detected in blood culture with no visceral manifestation [ 37 ].…”
Section: Cutaneous Leishmaniasismentioning
confidence: 99%
“…During active LCL, Leishmania parasites are not restricted to the skin lesions but are also detectable at extralesional sites including blood monocytes, tonsils and normal skin 83 84. Viable Leishmania parasites have also been found in scarred skin lesions and lymph nodes after clinical cure,8587 as well as in the blood of asymptomatically infected humans 8890.…”
Section: Infection Cycle Pathogenesis and Immunologymentioning
confidence: 99%
“…In a sample population ( n = 162), parasites were obtained from 85 patients (52.5%), and were isolated from the blood by cultures of 50 patients (30.9%). Isoenzyme analysis confirmed that the organisms in blood and skin were the same, which underlines the invasive potential of the parasite that escaped the skin [3]. …”
Section: Introductionmentioning
confidence: 97%